Perfil cognitivo aos sete anos de idade de crianças nascidas prematurase com peso inferior a 1.500 gramas - Alexandre Ferreira Campos (2009)
Objective: To know the cognitive development, at the age of seven, of preterm children born at the Hospital das Clínicas of the Federal University of Minas Gerais (HC/UFMG), with gestational age up to 34 weeks and weight at birth below 1500 grams, adequate to thegestational age. The children were longitudinally followed in an interdisciplinary approach at the High-Risk Children Outpatient Clinic ACRIAR and had normal intelligence and neurological exams at the age of seven. Methods: Forty-four children, aged seven, took part in the study, out of which 22 were preterm, born at the HC/UFMG and followed at ACRIAR. The other children, the control group, were selected due to their similar socioeconomic level, and were born at full term with weight adequate to the gestational age, without neonatal complications and had typical development according to parents and teachers. Children of the control group were recruited from a public school and paired with those from ACRIAR regarding sex, age, and schooling level . The cognitive development of children of both groups was analyzed byneuropsychological tests that assessed intelligence (Wechsler Intelligence Scale for Children-III); episodic memory (Reys Auditory-Verbal Learning Test and Complex Figure Test); andexecutive functions (Verbal Fluency Test, Tower of London Test, Wisconsin Card Sorting Test). Out of the 22 preterm children, 20 were assessed by the Lefèvre evolutive neurological exam. Mann-Whitney Us non-parametric test was used for comparing the neuropsychological test results between groups. Spearmans correlation coefficient was usedto examine the association between the neuropsychological evaluation and the evolutive neurological exam. Results: Children born preterm had IQ within the average for the age, but lower than the children born at full term. They performed worse, with statistical significance, in intelligencemeasurements (Total IQ, verbal IQ, execution IQ, verbal comprehension and processing speed) and planning, which are related to executive functions. The most pronounced differences were in verbal aspects and processing speed. There were no significant differences in episodic memory or other components of executive functions. Despite the normalneurologic exam, only 20% of the children born preterm performed all the exams of the evolutive neurological exam. Conclusion: This study highlights the value of specific cognitive evaluations in pretermchildren, even if they are apparently normal in the first years of life. This population needs to be followed at least until school age in longitudinal multidisciplinary programs, which would help to identify early developmental disorders and promote therapeutic interventionsaccordingly. The neurological development profile, obtained by the evolutive neurological exam might help in detecting children with difficulties that require further neuropsychological investigation. It is hoped that with the data from this study, health and education professionals are alerted to the late repercussions presented by preterm children born with very low weight.